A Probabilistic Approach to Pricing a Bundle of Products or Services - Venkatesh, R.; Mahajaim, Vijay (Journal of Marketing Research, 1993)
The authors propose a probabilistic approach to optimally price a bundle of products or services that maximizes seller's profits. Their focus is on situations in which consumer decision making is on the basis of multiple criteria. For model development and empirical investigation they consider a season ticket bundle for a series of entertainment performances such as sports games and music/dance concerts. In this case, they assume consumer purchase decisions to be a function of two independent resource dimensions, namely, available time to attend performances and reservation price per performance. Using this information, the model suggests the optimal prices of the bundle and/or components (individual performances), and corresponding maximum profits under three alternative strategies: (a) pure components (each performance is priced and offered separately), (b) pure bundling (the performances are priced and offered only as a bundle), and (c) mixed bundling (both the bundle and the individual performances are priced and offered separately). They apply their model to price a planned series of music/dance performances. Results indicate that a mixed bundling strategy is more profitable than pure components or pure bundling strategies provided the relative prices of the bundle and components are carefully chosen. Limitations and possible extensions of the model are discussed.